PENGARUH KEPEMIMIPINAN DAN KOMUNIKASI TERHADAP KINERJA PEMERINTAHAN KABUPATEN SIDENRENG RAPPANG PERIODE 2018 -2023 - Anastasia D'Ornay; Maskur Hasan (Jurnal Ilmu Manajemen Profitability, 2019)
Abstract The objectives of this study are (1) to find out partially the influence of leadership and communication dimensions used by the Government of Sidenreng Rappang Regency. (2) To determine simultaneously the influence of leadership and communication dimensions used by the Government of Sidenreng Rappang Regency. Data collection techniques that researchers use in this study are interviews, questionnaires and literature study. As the population in this study, researchers took elements of structural positions ranging from echelon II.B to Echelon III.A totaling 182 people. In order for this research to be precise and proportional, a sampling technique using the Slovin formula was used so that the calculation results narrowed the sample of this study to 42 people which the researchers randomly took from representatives of 14 offices to the Dinas and 11 Subdistricts that were in direct contact with regional development. The results of this study indicate that (1) Leadership partially affects the performance of the Government of Sidenreng Rappang Regency where the results obtained by leadership have a t-count value of 2.320 from t table 1.684 and the significance level is less than 0.05 (sig=0.0020.05 ). (2) Communication style partially affects the performance of the Government of Sidenreng Rappang Regency where the results obtained by the communication style have a t-count value of 2.066 from t table 1.684 and the level of significance is less than 0.05 (sig = 0.004 0.05). (3) Leadership and communication style simultaneously (simultaneously) also affect the performance of the Government. This can be seen from the Fcount value of 131.925 which is greater than the F table, which is 3.23 with a probability value of 0.000 which means it is still below the 0.05 significance value.